Strategi dan Kualitas Terjemahan Kitab Bidāyatul-Hidāyah Karya Imam Al-Ghazali (Upaya Menangkal Degradasi Moral Bangsa Berbasis Kajian Terjemahan Kitab Keagamaan) - Muhamad Saiful Mukminin; Justicia Shabirina Kusumadewi; Khoirunnisa Rahmawati; Meilinda Ika Susanti; Muhammad Yunus Anis (Diwan : Jurnal Bahasa dan Sastra Arab, 2023)
The purpose of this article is to determine the use of translation strategies and the assessment of translation quality in the translation of the Arabic-Indonesian book of Bidāyatul-Hidāyah. The descriptive qualitative research method was used in this study. The data in this study are sentences containing moral values from the book Bidāyatul-Hidāyah and its Indonesian translation. Data were gathered using two methods: listening and recording, as well as a questionnaire. Based on an analysis of 60 data points, three types of translation strategies were identified: syntactic translation strategies (62.8%), semantic translation strategies (8.3%), and pragmatic translation strategies (28.9%). The translation quality assessment results are classified as less accurate, less acceptable, and medium readability, with a final average score of 2.58. The use of syntactic translation strategies can improve the accuracy, acceptability, and readability of translation results. مستخلص تهدف هذه الدراسة إلى تحديد تطبيق استراتيجيات الترجمة وتقييم جودة الترجمة في ترجمة كتاب بداية الهداية من العربية إلى الإندونيسية. إن منهج البحث المستخدم في هذا البحث هو المنهج الوصفي النوعي. البيانات الواردة في هذه الدراسة عبارة عن جمل تحتوي على قيم أخلاقية في كتاب بداية الهداية وترجمته باللغة الإندونيسية. تم جمع البيانات باستخدام تقنيتين، وهما الاستماع والتسجيل والاستبيانات. بناءً على تحليل ستين بيانا، وجد أن تطبيق ثلاثة أنواع من استراتيجيات الترجمة، وهي استراتيجيات الترجمة النحوية)٪ ٦٢٬٨) ، واستراتيجيات الترجمة الدلالية )٪٨٬٣) ، والاستراتيجيات العملية )٪٢٨٬٩). يتم تضمين نتائج تقييم جودة الترجمة في المستوى الأقل دقة، والأقل قبولًا، والمستوى المتوسط ​​من المقروئية بمتوسط ​​نهائي يبلغ ٢٬٥٨. إن تنفيذ إستراتيجية الترجمة النحوية قادر على جعل نتائج الترجمة دقيقة ومقبولة ومستوى عالٍ من قابلية القراءة. الكلمات المفتاحية: إستراتيجية الترجمة؛ جودة الترجمة؛ القيمة الأخلاقية؛ كتاب بداية الهداية